The Effect of Profitability, Solvability, Company Size, And Financial Distress on Audit Delay (Case Study of Property and Real Estate Companies Listed on the Indonesia Stock Exchange 2020-2023) - Lubna, Arzheti Zalfa; Dewi, Indah Permata (Majapahit Journal of Islamic Finance and Management, 2025)
This quantitative study examines the partial effects of profitability (measured by Return on Assets - ROA), solvency (measured by Debt-to-Asset Ratio - DAR), company size (represented by the natural logarithm of total assets), and financial distress (represented by Altman Z-Score) on audit delays in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A purposive sampling technique was used to extract data from a population of 92 listed companies, resulting in a final sample of 23 companies. The analysis was conducted using multiple linear regression analysis through SPSS version 25. The findings indicate that profitability (ROA) has a statistically significant partial effect on audit delays. In contrast, solvency (DAR), company size, and financial distress (Altman Z-Score) do not have a statistically significant effect on audit delays in the studied companies during the observation period.